Effects of gender and personality on experience of small living spaces: Ceiling height and floor plan shape in virtual environment - Lee, Seo-Young; Yoon, So-Yeon (Frontiers in Virtual Reality, 2022)
Virtual reality (VR) technology has been used as a design research tool to enable a virtual experience of a space as a real-life-scale mock-up. In terms of user experience design research, VR is highly scalable and adjustable, meaning that designed virtual prototypes and environments can be tested on a diverse population without restrictions. Given that the structural and spatial parameters are changeable, more systematic experiments are available in a controlled, virtual environment to understand user experiences and preferences. In spatial design, VR has been applied in various spaces, such as healthcare, retail, and workplace environments, often focusing on behavioral intentions and psychological perceptions. Among diverse spaces, small living spaces are gaining more popularity as an affordable housing solution and an environmentally sustainable lifestyle. Despite their growing demand, user experiences of small living spaces have not been empirically tested. Specifically, the impact of users’ different characteristics on the psychological responses to small living spaces has been rarely studied. In this study, we used three-dimensional (3D) virtual mock-ups to test how subjects of different genders and personality types perceived different shapes of a small space. A 2 × 2 factorial design was used to test two different wall length-width combinations (short vs. long floor plan shape) with two different ceiling heights (low vs. high). The results showed that participants reported greater place attachment to the space with a shorter floor plan than the longer one. In addition, the impact of the floor plan shape of the space on place attachment differed according to gender and personality.